Application of a Sulfur Removal Hydrometallurgical Process in a Lead-Acid Battery Recycling Plant in Costa Rica - Navarro-Monge, Marta (2017)
This study presents the implementation of a desulphurization process for lead recycling under different chemical and physical conditions using pyro-metallurgical processes. Desulphurization was done using a hydrometallurgical process using sodium carbonate as a desulphurization agent and different lead bearing loads compositions. Waste characterization included: SO2 concentrations in the stack emissions, total lead content in the furnace ash, the total lead content in the slag, and the toxicity characteristic leaching procedure (TCLP). A significant reduction in SO2 emissions was achieved (~55% reduc tion) where mean SO2 concentrations changed from 2193 ± 135 ppm to 1006 ± 62 ppm after the implementation of the modified processes. The desulfurized lead paste (i.e. the metallic fraction lead of the battery) of the modified process exhibited an improvement in the concentration of the lead in the TCLP test, with an average value of 1.5 ppm which is below US EPA limit of 5 ppm. The traditional process TCLP mean value for the TCLP was 54.2 ppm. The total lead content in the bag house ashes shows not significant variations, when comparing the desulphurization (67.6% m/m) and non-desulphurizationvprocess (64.9% m/m). The total lead mean content in the slag was higher in the desulphurization process (2.49% m/m) than the traditional process (1.91% m/m). Overall, the implementation of a new esulphurization method would potentially increase the operation costs in 10.3%. At the light of these results, a combination of hydrometallurgical and pyro-metallurgical processes in the recycling of lead-acid batteries can be used to reduce the environmental im pact of these industries but would increase the operational costs of small lead recyclers.